2017
DOI: 10.5935/2359-4802.20170024
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Lifestyle of University Students in the Healthcare Area Using the Fantastic Questionnaire

Abstract: Background: The constant concern about quality of life nowadays has incited individuals to seek parameters for disease prevention. Along with that, arise a need to investigate and the ability to measure elements that characterize an appropriate lifestyle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1
14

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 2 publications
1
15
1
14
Order By: Relevance
“…However, it should be noted that social and personal factors have an impact on how students experience this transition. In the study developed by Tassini et al (2017), students had difficulty in reconciling leisure, sleep, free time, and activities demanded by the university, and reported feeling tired and stressed with the daily routine, which is in line with the results of this study in what concerns the correlation between the domains of Physical Activity/Affiliation, Nutrition, Sleep/Stress, Work/Type of personality, and Insight. Thus, individuals who have better sleep quality and a greater stress management ability are happier and more optimistic and positive about life.…”
Section: Discussionsupporting
confidence: 87%
“…However, it should be noted that social and personal factors have an impact on how students experience this transition. In the study developed by Tassini et al (2017), students had difficulty in reconciling leisure, sleep, free time, and activities demanded by the university, and reported feeling tired and stressed with the daily routine, which is in line with the results of this study in what concerns the correlation between the domains of Physical Activity/Affiliation, Nutrition, Sleep/Stress, Work/Type of personality, and Insight. Thus, individuals who have better sleep quality and a greater stress management ability are happier and more optimistic and positive about life.…”
Section: Discussionsupporting
confidence: 87%
“…The aim of this study was to analyse the lifestyle of the elderly aged 65+ with the use of the Fantastic Life Inventory (FLI) designed by Wilson, Nielsen and Ciliska [17]. Although this tool is also effectively used in research on the lifestyle of young people [18,19,20], to the best knowledge of the authors of the current study there is no research with the use of this tool among people aged 65+. Additionally, to-date the FLI has not been used in Poland.…”
Section: Objectivementioning
confidence: 99%
“…Not following a healthy lifestyle is a risk factor of modern civilization diseases because the health of an individual is mainly determined by their individual health behaviours [26,28]. It is estimated that the main cause of death in developing and developed countries are cardiovascular diseases [4,13].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is currently believed that the most effective method of reducing the epidemiological risk of cardiovascular diseases is adequate prevention. Assessment of cardiovascular risk and attempts to modify or eliminate existing risk factors in individual patients are basic preventive measures [18,20,21,22].To-date, research has shown that a healthy lifestyle is a decisive factor in maintaining and strengthening public health [23,24,25,26,27].…”
Section: Introductionmentioning
confidence: 99%